1956
DOI: 10.1149/1.2430182
|View full text |Cite
|
Sign up to set email alerts
|

Electroplating Engineering Handbook

Abstract: America's [argesf Manufacfurer-Distrlbufor of b~boratory Appliances and Reagenf Chemicals ) unless CC License in place (see abstract). ecsdl.org/site/terms_use address. Redistribution subject to ECS terms of use (see 128.122.253.228 Downloaded on 2015-06-04 to IP ) unless CC License in place (see abstract). ecsdl.org/site/terms_use address. Redistribution subject to ECS terms of use (see 128.122.253.228 Downloaded on 2015-06-04 to IP

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…3 The data from this study confirm the low emissions from nickel sulfate (Watts) baths and show equally low emissions from nickel sulfamate baths.…”
Section: Copper Platingsupporting
confidence: 74%
See 1 more Smart Citation
“…3 The data from this study confirm the low emissions from nickel sulfate (Watts) baths and show equally low emissions from nickel sulfamate baths.…”
Section: Copper Platingsupporting
confidence: 74%
“…2 In the case of electroless plating the barrels can be constructed from "Lucite", or polypropylene because no electrical connections are required. 3 The manual or vat process incorporates a series of tanks that contain the appropriate cleaning and plating solutions.…”
Section: Mechanical Processesmentioning
confidence: 99%
“…7 It is evident that ammoniacal platting baths produce the desirable bottom-up or super filling behavior in trenches and vias. 8 In previous studies, [8][9][10] it has been shown that a composition of ammonia, copper sulfate, and ammonium sulfate is successful in copper plating. However, the same chemistry is found to be too corrosive for the W 2 N and it dissolves "Seedless" Electrochemical Deposition of Copper on Physical Vapor Deposition-W 2 N Liner Materials for ULSI Devices 1603 the barrier before full copper coverage can be obtained.…”
Section: Resultsmentioning
confidence: 99%
“…Each needle was then manually bent at 90° out of the plane of the sheet. The needles were electropolished in a bath containing a 6:3:1 mixture by volume of glycerin, phosphoric acid, and water (Fisher Scientific, Atlanta, GA, USA) to remove debris (Graham 1971;Hensel, 2000). This electropolishing process reduced the needle thickness to 50 m.…”
Section: Microneedle Fabricationmentioning
confidence: 99%